The psychology of learning and motivation : advances in research and theory. - Ross, Brian H. (Psychology of learning and motivation, 2006)
Discusses the concepts of category learning, prototypes, prospective memory, event memory, memory models, and musical prosody. This work is intended for researchers and academics in cognitive science.